Antibacterial Activity of Acanthoic acid Isolated from Acanthopanax koreanum against Oral and Skin Microfloras - Jin Kyung Kim (동의생리병리학회지, 2006)
The (-)-pimara-9 (11), 15-dien-19-oic acid, acanthoic acid was extracted from the roots of Acanthopanax koreanum using bioassay-guided isolation of a MeOH extract. Acanthoic acid was assayed against Streptococcus mutans and Staphylococcus epidermidis causing dental caries and opportunistic pathogen. The minimum inhibitory concentration (MIC) of acanthoic acid against Streptococcus mutans and Staphylococcus epidermidis was 2 and 4 ㎍/mL, respectively, which was much lower than those of other natural antimicrobial agents such as 8 ㎍/mL of tanshinone IIA. Acanthoic acid also significantly inhibited the growth of other cariogenic bacteria such as Streptococcus sobrinus and Streptococcus sanguis, and Streptococcus gordonii in the MIC range of 4~32 ㎍/mL. Our findings suggest that acanthoic acid could be employed as a potential antibacterial agent for preventing dental caries and skin infections. KCI Citation Count: 1